Muscle quality index is correlated with insulin resistance and type 2 diabetes mellitus: a cross-sectional population-based study - Mengye Zhang; Hao Lin; Xue Xu (BMC Public Health)
Abstract Background Muscle quality index (MQI), an emerging health index, is calculated by dividing handgrip strength by skeletal muscle mass. Current evidence on the correlation between MQI and type 2 diabetes mellitus (T2DM), insulin resistance (IR) is limited. This work aims to study that correlation. Methods This study involves a cross-sectional analysis on data from the National Health and Nutrition Examination Survey (NHANES) during the period from 2011 to 2014. To explore the correlation between MQI, IR and T2DM, multivariate logistic regression, receiver operating characteristic (ROC) curve, subgroup analysis, and restricted cubic spline regression were employed. Results A total of 2816 American adults were enrolled in this study, among whom 1264 (44.9%) had IR, and 300 (10.7%) had T2DM. Logistic regression and RCS regression analyses showed a significant negative linearly correlation between MQI and the prevalence of IR (OR = 0.708, 95%=0.514, 0.976) and T2DM (OR = 0.676, 95%CI = 0.472, 0.969). Subgroup analysis further revealed a stronger correlation between MQI and IR among individuals with obesity. ROC analysis showed that compared with skeletal muscle and grip strength, MQI (AUC = 0.679 for IR and 0.688 for T2DM) can serve as a more reliable identification factor for IR and T2DM. Conclusion This study provides evidence that decreased levels of MQI are correlated with an increased risk of IR and T2DM, indicating the potential utility as a marker for identifying IR and T2DM.